Production by in vitro fertilization of vietnam swamp buffalo embryos - Ty, Le Van; Son, Hoang Nghia; Hung, Nguyen Mong (Academia Journal of Biology, 2014)
This study was undertaken in order to test the ability of replacement of the foetal bovine serum (FBS) supplemented with hormones by the buffalo follicular fluid (BFF) in the oocyte maturation medium and the effect of co-culture with oviduct cells on the subsequent embryo development in Vietnam swamp buffalo. 1400 cumulus enclosed oocytes (COC) were collected from the buffalo ovaries in slaughter-house in the way with minimize temperatural choc. COCs were randomtly cultured in three maturation medium varieties: TCM 199 supplemented with 10% FBS, 10 IU/ml eCG, 5 IU/ml hCG, 1 mg/ml estradiol (M1); TCM 199 with 20% buffalo follicular fluid (BFF) without hormones (M2) or TCM 199 with 20% BFF and the same level of eCG, hCG as M1 but 3 mg/ml estradiol (M3). The effect of oviduct cells was evaluated by the embryo co-culture in two medium varieties: synthetic oviduct fluid (SOF) and SOF with oviduct cells after the maturation in the medium M2 and IVF. No significal differences were observed in the maturation and the formation of morulas and blastocyts by using the routine maturation medium (M1) and TCM 199 supplemented with 20% BFF but the rate of formation of two-cell and more-cell embryos and the rate of total morula and blastocyts were clearly improved in the case of combined BFF and hormones (M3) (26.5% vs 16.3%, P < 0.05). The co-culture with oviduct cells not only improved the percentage of total embryos developed into morula blastocyt stage but also increased the rate of blastocyt formation in comparision with the medium without cells (66.2% vs 44.4%, P < 0.05). This first try of in vitro embryo production in the swamp buffalo indicated the comparable rate (approximately 20%) of blastocyts can be obtained from total using oocytes.